Analysis of The Influence of Perceived Usefulness Factors and Subjective Norm on Intention to Use QR Code of Digital Wallet Users - Djaniar, Upik; Sukriyadi; Munizu, Musran; Tomadehe, Sumiati; Ady Bakri, Asri (Jurnal Informasi dan Teknologi, 2024)
The purpose of this study is to ascertain how behavioral intention to reuse is influenced by perceived usefulness, perceived ease of use, compatibility, subjective norm, perceived risk, perceived trust, and perceived cost of the QR payment. The researcher employed a survey approach, a single cross-sectional design for data collecting, and a conclusive research design with a descriptive research design type. Researchers employed the judgmental sampling method along with non-probability sampling strategies in this study. There were 100 samples used in this investigation. major data from the outcomes of distributing questionnaires served as the major data source. Researchers used the structure-equation modeling (SEM) technique to evaluate their hypothesis. The study's findings indicate that behavioral intention to utilize QR Code payments is positively influenced by perceived usefulness, perceived simplicity of use, compatibility, subjective norms, and perceived trust. An individual's intention to use the service again is positively correlated with how much they perceive the benefits, find it easy to use, find it matches their lifestyle, have support from significant others, and have a high degree of faith in the QR Code. Perceived risk and cost, however, do not significantly affect behavioral intention, indicating that people's intentions to use QR Codes again are not hampered by their sense of risk and associated expenses.